P01.01 A Phase 1a/1b dose-escalation study of intravenously administered SB 11285 alone and in combination with nivolumab in patients with advanced solid tumors. (1st October 2020) - ABBAS, A; Strauss, J; Janku, F; Karim, R; Olszanski, A; Luke, JJ; Leach, K; Iyer, R
Abstract : Background: Immunotherapy has emerged as a transformative approach for the treatment of cancer. However, a significant percentage of patients are nonresponsive to these immunotherapies or experience disease relapse which highlights the need for new therapies. Recent work has highlighted a major role for Stimulator of Interferon Genes (STING ) agonists in immunotherapy. Conceptually, the activation of the STING pathway in immune cells in the tumor microenvironment (TME) and tumor cells could result in the induction of innate and adaptive immunity and subsequent activation of cytotoxic T cells and NK cells for durable anti-tumor responses. SB 11285 is a novel agonist of STING pathway leading to the activation of tumor-resident APCs and priming of tumor antigen specific CD8+ T cells. In our preclinical studies using multiple tumor-derived cell lines, SB 11285 has been observed to cause the induction of cytokines, such as INF-b, INF-a, TNFa and others consistent with engagement of the STING target, as well as tumor cell death by STING-mediated apoptosis. SB 11285 reduced tumor volumes in multiple rodent tumor models when administered intravenously, intraperitoneally and intratumorally. Systemic administration could additionally facilitate trafficking of newly activated CD8+T cells from periphery into the tumor site. In addition, preclinical models indicate that survival and local tumor shrinkage were significantly enhanced when SB11285 was administered with anti-CTLA-4 or anti-PD-1 antibody, suggesting that SB 11285 can be administered with anti-PD-1 and anti-CTLA-4 antibody for synergistic activity. A multiple ascending dose, phase 1a/1b trial of SB11285 in multiple tumor types has been initiated and the objectives of this trial include determining a safe and efficacious dose of intravenous SB 11285 and a preliminary assessment of antitumor activity/efficacy as either monotherapy or in combination with nivolumab. Materials and Methods: This open-label, multicenter phase 1a/1b clinical trial (NCT04096638 ) aims to enroll approximately 110 patients in the dose escalation (Part 1) and expansion cohorts (Part 2). Part 1 of the trial is a dose escalation study with IV SB11285 monotherapy followed by combination with the checkpoint inhibitor nivolumab. Part 1 Dose Escalation of the study will evaluate ascending doses of intravenously administered SB 11285 with respect to dose-limiting toxicities (DLTs), maximum tolerated dose (MTD), recommended phase 2 dose (RP2D) and the pharmacokinetic (PK)/pharmacodynamic profile as monotherapy and in combination with nivolumab. SB 11285, with a starting dose of 0.3 μg/kg, will be administered as monotherapy weekly on Days 1, 8, 15, and 22 of repeated 28-day cycles in escalating doses and in combination with nivolumab administered on Q4W schedule. Part 2 Expansion Cohorts of the study will explore initial signs of efficacy in pre-specified tumor types (such as Melanoma, HNSCC) using the recommended phase 2 dose (RP2D) of SB 11285 in combination with nivolumab. In addition, the biological effects of SB 11285 will be evaluated by changes in immune cell types and activation state, serum cytokines, and gene expression patterns indicative of activation of the immune compartment. The trial is being conducted at multiple sites in the U.S. Disclosure Information: A. Abbas: A. Employment (full or part-time); Modest; Spring Bank Pharmaceutical Inc. J. Strauss: E. Ownership Interest (stock, stock options, patent or other intellectual property); Modest; Abbvie, Abbott Laboratories, Bristol-Myers Squibb, Intuitive Surgical, Johnson & Johnson, Merck. F. Consultant/Advisory Board; Modest; Tempus. Other; Modest; Dialectic Therapeutics. F. Janku: None. R. Karim: None. A. Olszanski: F. Consultant/Advisory Board; Modest; Bristol Myers Squibb. J.J. Luke: B. Research Grant (principal investigator, collaborator or consultant and pending grants as well as grants already received); Modest; All to institution for clinical trials unless noted) Abbvie, Bristol Myers Squibb, Medimmune, Necktar, Novartis, Merck, Leap, Incyte, Immunocore, Compugen, Corvus, Evil, Five Prime, Genentech, Immatic. F. Consultant/Advisory Board; Modest; Consultant:Akrevia, Algios, Array, Astellas, AstraZeneca, Bayer, Bristol Myers Squibb/Advisory Board:7 Hills, Actym, Alphamab Oncology, Mavu (now part of Abbvie), Pyxis, Spring Bank Pharma, Tempest. Other; Modest; Travel: Akrevia, Bayer, Bristol Myers Squibb, Reflexion, EMD Serono, Incyte, Janssen, Merck, Mersana, Novartis. K. Leach: A. Employment (full or part-time); Modest; Spring Bank Pharmaceuticals Inc. R. Iyer: A. Employment (full or part-time); Modest; Spring Bank Pharmaceuticals Inc.